ANALYSIS OF FACTORS AFFECTING CAESAREAN SURGERY DELIVERY IN THE PRACTICE OF MIDWIFE NURHAYANI NASUTION, KAMPUNG RAKYAT DISTRICT, SOUTH LABUHANBATU REGENCY IN 2023 - Khadijah, Nur Khadijah; Rosmani Sinaga; Lisa Putri Utami Damanik; Hazizah Sabilah Siagian; Kismiasih Adethia; Supini; Irma Wati (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
The number of deliveries by cesarean section (CS) continues to increase, including in primary healthcare settings such as independent midwifery practices. This is concerning because the World Health Organization (WHO) recommends an ideal cesarean section rate of around 10–15% of all deliveries. Independent midwife Nurhayani Nasution’s practice in Kampung Rakyat District, South Labuhanbatu Regency, showed an increase in referrals for cesarean deliveries during 2023. This research is quantitative, using statistical techniques to measure something. The process of seeking knowledge that uses numerical data as a tool to analyze what one wants to know is called quantitative research methodology.(Sujarweni, 2022)The method used in this study is analytical with a cross-sectional approach, which examines the dynamics of the correlation between risk factors and their effects through observation or collective data collection. This study aims to analyze the factors influencing the decision or referral for cesarean section delivery by independent midwives. Factors influencing CS delivery include medical factors (history of previous CS, preeclampsia, CPD, fetal distress), sociocultural factors (family request, fear of pain), and service factors (the midwife’s ability to detect complications). A history of previous CS was the dominant factor (30%), followed by family request (20%). CS deliveries in independent midwifery practices are influenced by various factors, both clinical and non-clinical. An educational approach and improved communication between midwives and patients are needed to ensure that CS decisions are based on appropriate medical indications.